Attitude Among Medical Students of the College of Health and Medical Techniques Baghdad Regarding Drug Abuse - Noor Al-huda Anwar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The study was conducted at Middle Technical University (College of Health & Medical Techniques, Baghdad) from 29Th October 2024 to 15Th January 2025, enrolling 148 students aged 20–24 years (47.3%), 25–29 years (41.9%), 30–39 years (9.5%), and over 40 years (1.4%), Participants completed a structured questionnaire to assess attitudes toward drug abuse. Regarding protective attitudes, 66.2% agreed that educational programs aid prevention, 68.9% viewed better education as protective, 58.8% cited close family ties, and 72.2% recommended avoiding friends who use drugs, Departmental analysis showed the highest proportion of ―good knowledge in Anesthesia Techniques (95.3%) and the lowest in Physical Therapy Techniques (80.2%) While overall awareness of drug abuse is high among health and medical students, misconceptions regarding its symptoms and effects persist. Targeted educational interventions—especially within departments showing lower knowledge—and reinforcement of accurate prevention and treatment strategies are recommended to strengthen students’ competencies in addressing drug abuse.